CODE MIXING OF BEAUTY VLOGGER ON INSTAGRAM - Lutfah Fadilah Nispi; Silpia Rahayu (IKIP Siliwangi, 2023)
The research aim to find out the phenomena of beauty vloggers and their code mixing. Nowadays some beauty vloggers attract viewers by using two or more languages, in English study it is called code mixing. In order to accomplish research objective the research use quatitative research design. The instrument use in this research were document analysis. The research subject of this research was beauty vloggers Tasya Farasya, Rachel Goddard and Ini Vindy in their Instagram videos. The researchers was finding 9 data with two various of code mixing that is insertion (2 data or 22,2%) and alternation (7 data or 77,8%) that the beauty vloggers used in their Instagram videos. The result of this study showed that beauty vloggers highest frequency used is Alternation type code mixing, while the lowest frequency used is Insertion type of code mixing. The implication of this research is to improve beauty vloggers English skill and increase viewers English vocabulary and pronounciation. Keywords: Beauty Vlogger; Code Mixing; Instagram